การศึกษาอัตราการกลายพันธุ์ของเครื่องหมาย Y-STR ที่กลายพันธุ์รวดเร็วจำนวน 4 ตำแหน่งในคู่บิดาและบุตรชายไทย - ธมลวรรณ โชติกรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
Y-chromosomal short tandem repeats (Y-STRs) are common DNA markers frequently used in forensic fields to investigate paternal lineage and identify male perpetrators in cases of sexual assault. However, commercial Y-STR kits typically fail to differentiate in same lineage due to low to moderate mutation rate. DYF399S1, DYS547, DYF403S1a, and DYS612 were classified as rapidly mutating Y-STR (RM) in which different mutation rate occurs between ethnic groups. There is a lack of information RM Y-STR in Thailand, and the mutation rate of RM Y-STR needs to be reported to support Y-STR haplotype studies in the future. The present study was conducted to determine the mutation rate of four RM Y-STR candidates and compare mutation rate of Thai population with other population. This study included 240 blood samples of father and son pairs on FTA. One 1.2 mm disc of the FTA card was purified and amplified with a specific primer that qualifies for a validation test. After that, the amplicons size were separated via capillary electrophoresis and a DNA profile was generated by Gene Mapper Software. Then, the father’s DNA profile was compared with offspring’s profile and the mutation was directly determined by repeat unit changes. Finally, the mutation rate of four candidate markers was calculated. The mutation rate of DYF399S1 was 6.7 x 10-2per locus per gamete per generation, making it the most highly mutated marker in this study.        In addition, the mutation rate of DYF403S1a was 2.1 x 10-2 per locus per generation, while the mutation rate of DYS612 was also 2.1 x 10-2 per locus per gamete per generation. The mutation rate of DYS547 was 4 x 10-3 per locus per gamete per generation, making it moderately mutated in the Thai population. The mutation rates of these markers in the Thai population were different but not significantly (Pvalue = 0.05). Furthermore, the father s age at the son s birth showed a significant difference (Pvalue = 0.003). We hope the findings of this study will promote more research and eventually extend the body of RM Y-STRs population data.